Repairing method for surface thermal performance of quartz component

By etching treatment, the surface defects and impurity layers of quartz parts are removed using solutions such as hydrofluoric acid or sodium hydroxide, the thermal stability and roughness problems after sandblasting are solved, and the thermal performance and adhesion of quartz parts are restored, thus achieving the realization of the thermal performance and adhesion of quartz parts. Thermal performance repair of quartz parts.

CN119282926AInactive Publication Date: 2025-01-10ZJU HANGZHOU GLOBAL SCI & TECH INNOVATION CENT
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411702587.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

After sandblasting, the thermal stability of quartz parts is reduced, and surface defects and impurities affect their thermal properties and surface roughness, and there is a lack of effective repair methods.

Method used

The mixture of hydrofluoric acid, sodium hydroxide or ammonium fluoride and oxalic acid dihydrate and water is etched to remove subsurface defects and residual impurities, restore the softening temperature and thermal performance of quartz parts, while maintaining the surface roughness. Spend.

Benefits of technology

Effectively improve the surface finish and purity of quartz parts, restore softening temperature, enhance thermal performance, and ensure the adhesion of surface accumulations to avoid particles falling off.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154003980000101
    Figure BDA0005154003980000101
  • Figure BDA0005154003980000111
    Figure BDA0005154003980000111
Patent Text Reader

Abstract

The invention relates to a method for repairing the thermal performance of the surface of a quartz part. The repairing method comprises the following steps: carrying out sand blasting treatment on a quartz part, and carrying out first cleaning and first blow-drying; carrying out etching treatment on the quartz part subjected to sand blasting treatment, and carrying out secondary cleaning and secondary blow-drying to obtain a repaired quartz part; wherein an etching solution adopted in the etching treatment is a mixed solution of hydrofluoric acid, first acid and water, or a mixed solution of sodium hydroxide and water, or a mixed solution of ammonium fluoride, oxalic acid dihydrate, first acid and water. According to the repairing method, subsurface defects and residual impurity layers generated in the sand blasting process are effectively removed, the damage starting point of the quartz part under the high-temperature operation condition is blocked, the surface smoothness and purity are improved, the softening temperature of the quartz part is effectively recovered, the thermal performance of the surface of the quartz part is improved, and the service life of the quartz part is prolonged. And meanwhile, the surface roughness of the quartz component is guaranteed, and the adhesive force of surface deposits of the quartz component is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of semiconductor quartz component surface treatment, in particular to a method for repairing the thermal properties of the surface of a quartz component. Background Art

[0002] At present, the semiconductor quartz processing industry usually uses sandblasting technology to process the surface of quartz parts to improve the surface roughness of quartz parts. Sandblasting technology mainly uses abrasive particles carried by high-speed airflow to impact the surface of quartz parts. After sandblasting, the surface of the quartz parts can form a concave-convex structure with a high roughness, which is conducive to adsorbing and maintaining the adhesion of deposits.

[0003] However, sandblasting may significantly reduce the thermal stability of quartz components, which is reflected in significantly reducing the softening temperature of quartz components and accelerating the aging process. This is mainly due to the physical damage and microstructural changes caused to the surface of quartz components by the sandblasting process. In high temperature environments, the performance of quartz components is often affected by their surface defects, and microcracks and sub-surface defects will become potential starting points for damage. These surface defects will not only affect the mechanical properties of quartz components to a certain extent, but may also aggravate the concentration of local stress. As a brittle material, quartz has a relatively low thermal expansion coefficient. Therefore, during the heating process, when there is surface inhomogeneity, the thermal expansion between different areas is inconsistent, which may cause the accumulation of thermal stress, resulting in a decrease in thermal stability.

[0004] At the same time, sandblasting can also adversely affect the thermal stability of quartz parts by changing the chemical properties of the surface. The abrasive used in sandblasting may remain on the surface of the quartz parts, affecting the surface purity of the quartz parts. During the sandblasting operation, the surface of the quartz parts may be exposed to various chemicals, such as acids and oxidizing substances, which may be deposited on the surface of the quartz parts and react chemically with the quartz, causing erosion of the surface of the quartz parts, thereby affecting its thermal stability.

[0005] At present, there are few reports on methods for repairing the thermal properties of the surface of quartz components after sandblasting. There is an urgent need for a method that can improve the surface roughness of quartz components and repair the thermal properties of the surface of quartz components. Summary of the invention

[0006] Based on this, it is necessary to provide a method for repairing the thermal properties of the surface of a quartz component to address the above-mentioned problems. The repair method provided by the present invention effectively removes the sub-surface defects and the residual impurity layer generated during the sandblasting process, blocks the starting point of damage to the quartz component under high-temperature working conditions, improves the surface finish and purity, effectively restores the softening temperature of the quartz component, improves the thermal properties of the surface of the quartz component, and effectively guarantees the surface roughness of the quartz component, and improves the adhesion of the surface deposits of the quartz component.

[0007] The present invention provides a method for repairing the thermal properties of a quartz component surface, comprising the following steps:

[0008] The quartz parts are sandblasted, cleaned for the first time and blown dry for the first time;

[0009] The quartz component after sandblasting is etched, and then cleaned and dried for the second time to obtain a repaired quartz component; wherein the etching solution used in the etching treatment is selected from a mixture of hydrofluoric acid, a first acid and water, or a mixture of sodium hydroxide and water, or a mixture of ammonium fluoride, oxalic acid dihydrate, a first acid and water.

[0010] In one embodiment, the surface roughness of the quartz component after sandblasting is 0.5 μm to 5 μm.

[0011] In one embodiment, the surface roughness of the quartz component after sandblasting is A μm, and the surface roughness of the quartz component after etching is B μm, wherein the absolute value of (AB) / A is less than or equal to 10%.

[0012] In one of the embodiments, the surface roughness of the quartz component after etching is 0.45 μm to 5.5 μm.

[0013] In one of the embodiments, the initial surface roughness of the quartz component is 0.1 μm to 0.2 μm.

[0014] In one embodiment, the etching solution includes 1% to 20% hydrofluoric acid, 1% to 50% first acid and the balance water;

[0015] Alternatively, the etching solution includes 0.1% to 1% sodium hydroxide and the balance water;

[0016] Alternatively, the etching solution includes 5% to 10% of ammonium fluoride, 5% to 10% of oxalic acid dihydrate, 1% to 50% of the first acid and the balance of water.

[0017] In one embodiment, the first acid is selected from at least one of nitric acid, hydrochloric acid, sulfuric acid and acetic acid.

[0018] In one of the embodiments, during the etching process, the temperature of the etching solution is 30° C. to 80° C.

[0019] In one embodiment, the etching process lasts for 10 minutes to 600 minutes.

[0020] In one embodiment, the first cleaning and the second cleaning are both performed with deionized water, and the cleaning time is independently selected from 10 min to 15 min;

[0021] And / or, the first drying and the second drying are both performed using protective gas.

[0022] The above-mentioned method for repairing the thermal properties of the surface of the quartz component performs etching treatment through a specific solution, and allows hydrofluoric acid (oxalic acid and ammonium fluoride slowly react to generate hydrofluoric acid) or sodium hydroxide to react with the quartz component, thereby effectively removing sub-surface defects generated during the sandblasting process and the residual impurity layer, blocking the starting point of damage to the quartz component under high-temperature operating conditions, improving the surface smoothness and purity, effectively restoring the softening temperature of the quartz component, and improving the thermal properties of the surface of the quartz component. At the same time, it effectively protects the surface roughness of the quartz component and improves the adhesion of the surface deposits of the quartz component.

[0023] Therefore, the method for repairing the thermal properties of the surface of a quartz component provided by the present invention effectively improves the surface roughness of the quartz component and can repair the thermal properties of the surface of the quartz component at the same time, and the process is simple and has broad application prospects. DETAILED DESCRIPTION

[0024] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments or embodiments, and are not intended to limit the present invention. The optional range of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the arbitrary and all combinations include any two related listed items, any more related listed items, or all related listed items. In the present invention, it is related to a numerical range. If there is no special explanation, the above numerical range is regarded as continuous and includes the minimum and maximum values ​​of the range, and each value between such minimum and maximum values. Further, when the range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the range can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges included therein.

[0026] After long-term and in-depth research, the applicant found that the physical damage and microstructural changes caused by the sandblasting treatment used in the industry to the surface of the quartz parts will lead to the deterioration of the performance of the surface of the quartz parts. Microcracks and sub-surface defects will not only affect the mechanical properties of the quartz parts to a certain extent, but may also aggravate the concentration of local stress. Quartz, as a brittle material, has a relatively low thermal expansion coefficient. Therefore, during the heating process, when there is unevenness on the surface, the thermal expansion between different regions is inconsistent, which may cause the accumulation of thermal stress, thereby causing a decrease in thermal stability. At the same time, sandblasting can also adversely affect the thermal stability of the quartz parts by changing the chemical properties of the surface. The abrasive used in sandblasting may remain on the surface of the quartz parts, affecting the surface purity of the quartz parts. During the sandblasting operation, the surface of the quartz parts may be exposed to various chemical substances, such as acidic substances and oxidizing substances. These chemical substances may be deposited on the surface of the quartz parts and react chemically with quartz, causing the surface of the quartz parts to be eroded, thereby affecting its thermal stability.

[0027] Based on this, the present invention provides a method for repairing the thermal properties of the surface of a quartz component, comprising the following steps:

[0028] S1, sandblasting the quartz parts, and performing the first cleaning and the first drying;

[0029] S2, etching the quartz component after the sandblasting treatment, and performing a second cleaning and a second drying to obtain a repaired quartz component; wherein the etching solution used in the etching treatment is selected from a mixture of hydrofluoric acid, a first acid and water, or a mixture of sodium hydroxide and water, or a mixture of ammonium fluoride, oxalic acid dihydrate, a first acid and water.

[0030] The above-mentioned method for repairing the thermal properties of the surface of the quartz component performs etching treatment through a specific solution, and allows hydrofluoric acid (oxalic acid and ammonium fluoride slowly react to generate hydrofluoric acid) or sodium hydroxide to react with the quartz component, thereby effectively removing sub-surface defects generated during the sandblasting process and the residual impurity layer, blocking the starting point of damage to the quartz component under high-temperature operating conditions, improving the surface smoothness and purity, effectively restoring the softening temperature of the quartz component, and improving the thermal properties of the surface of the quartz component. At the same time, it effectively protects the surface roughness of the quartz component and improves the adhesion of the surface deposits of the quartz component.

[0031] Therefore, the method for repairing the thermal properties of the surface of a quartz component provided by the present invention effectively improves the surface roughness of the quartz component and can repair the thermal properties of the surface of the quartz component at the same time, and the process is simple and has broad application prospects.

[0032] In addition, quartz is a brittle material. After sandblasting, microscopic cracks will be generated at the "valley" position of the surface of the quartz component. These cracks will continue to break, extend, and expand during subsequent cleaning and even use, and particles are prone to continuous shedding during subsequent use. The surface thermal performance repair method provided by the present invention can effectively remove the sub-surface defects and residual impurity layers generated during the sandblasting process, blocking the starting point of damage to the quartz component under high-temperature working conditions. Therefore, the repair method of the present invention can also avoid the phenomenon of continuous shedding of quartz particles caused by sandblasting.

[0033] In step S1, the roughness of the surface of the quartz component is increased by sandblasting. Specifically, the initial surface roughness of the quartz component is 0.1 μm to 0.2 μm, including but not limited to any point value among 0.1 μm, 0.15 μm, 0.18 μm, 0.2 μm or any range value between two of them.

[0034] In one embodiment, the surface roughness of the quartz component after sandblasting is 0.5μm to 5μm, and the surface roughness includes but is not limited to any point value among 0.5μm, 0.6μm, 0.8μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, and 5μm, or a range value between any two of them, which is conducive to the adsorption of deposits on the surface of the quartz component and maintaining the adhesion of deposits.

[0035] It should be noted that the present invention has no special restrictions on the material and particle size of the abrasive particles used in the sandblasting process, as long as the roughness of the surface of the quartz part after sandblasting can reach the target roughness. Those skilled in the art can select the material and particle size of the abrasive particles according to actual needs.

[0036] In one embodiment, the first cleaning is performed with deionized water, and the cleaning time is selected from 10 min to 15 min, including but not limited to any point value among 10 min, 11 min, 12 min, 13 min, 14 min, 15 min or any range value between two of them.

[0037] It should be noted that the present invention has no special restrictions on the above-mentioned cleaning method, for example, cleaning can be performed by flushing; the present invention has no special restrictions on the temperature of the first cleaning, and those skilled in the art can choose according to actual needs. In order to reduce costs, the present invention preferably performs cleaning at room temperature.

[0038] In one embodiment, the first drying and the second drying are both performed using protective gas.

[0039] Preferably, the protective gas is selected from nitrogen.

[0040] In step S2, the quartz component after sandblasting is etched by a specific solution, and hydrofluoric acid (oxalic acid and ammonium fluoride slowly react to generate hydrofluoric acid) or sodium hydroxide reacts with the quartz component to effectively remove the sub-surface defects and residual impurity layer generated during the sandblasting process, thereby blocking the starting point of damage to the quartz component under high-temperature working conditions, improving the surface finish and purity, effectively restoring the softening temperature of the quartz component, and improving the thermal properties of the surface of the quartz component. At the same time, the surface roughness of the quartz component is effectively guaranteed, and the adhesion of the surface deposits of the quartz component is improved.

[0041] In one embodiment, the surface roughness of the quartz component after sandblasting is Aμm, and the surface roughness of the quartz component after etching is Bμm, wherein the absolute value of (AB) / A is less than or equal to 10%, which is beneficial to maintaining the surface roughness of the quartz component and further maintaining the adhesion of the surface deposits of the quartz component.

[0042] It can be understood that the ratio of the absolute value of the difference between A and B to A is less than or equal to 10%, and the surface roughness of the quartz component after etching is slightly different from the surface roughness of the quartz component after sandblasting.

[0043] Preferably, the surface roughness of the quartz component after etching is 0.45μm to 5.5μm, including but not limited to 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.8μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, any point value or any range value between two of them, which is conducive to the adsorption of the surface of the quartz component and maintaining the adhesion of deposits.

[0044] In one embodiment, the etching solution includes 1% to 20% hydrofluoric acid (HF), 1% to 50% of a first acid and the remainder of water, which is beneficial to further improve the removal effect of sub-surface defects and residual impurity layers, improve the surface finish and purity of the quartz component, restore the softening temperature of the quartz component, improve the thermal properties of the surface of the quartz component, and at the same time help to ensure the surface roughness of the quartz component, thereby further improving the adhesion of surface deposits on the quartz component.

[0045] In another embodiment, the etching solution includes 0.1% to 1% of sodium hydroxide (NaOH) and the balance of water.

[0046] In another embodiment, the etching solution includes 5% to 10% of ammonium fluoride, 5% to 10% of oxalic acid dihydrate, 1% to 50% of the first acid and the balance of water.

[0047] It should be noted that the above percentages are expressed as the mass fractions of the solutes in the etching solution.

[0048] Preferably, the first acid is selected from at least one of nitric acid (HNO3), hydrochloric acid (HCl), sulfuric acid (H2SO4) and acetic acid (CH3COOH), which is beneficial to remove the water-insoluble fluorosilicate precipitate generated by the reaction of hydrofluoric acid and the quartz component, thereby further improving the surface finish and purity of the quartz component.

[0049] In one embodiment, during the etching treatment, the temperature of the etching solution is 30°C to 80°C, including but not limited to any point value of 30°C, 35°C, 38°C, 40°C, 45°C, 50°C, 53°C, 55°C, 58°C, 60°C, 70°C, and 80°C, or a range of values ​​between any two of them, which is beneficial to improving the reaction efficiency of the etching solution with the quartz component after the sandblasting treatment, further improving the removal effect of sub-surface defects and residual impurity layers, improving the surface smoothness and purity of the quartz component, restoring the softening temperature of the quartz component, and improving the thermal properties of the surface of the quartz component. At the same time, it is beneficial to ensure the surface roughness of the quartz component, thereby further improving the adhesion of the surface deposits of the quartz component.

[0050] It can be understood that during the etching process, the temperature of the etching solution is adjusted to 30° C. to 80° C., and the quartz component after the sandblasting process is completely immersed in the etching solution for etching.

[0051] In one embodiment, the etching treatment time is 10 min to 600 min, including but not limited to any point value among 10 min, 20 min, 50 min, 80 min, 100 min, 200 min, 300 min, 400 min, 500 min, 600 min or any range value between two thereof, which is conducive to ensuring the etching effect.

[0052] In one embodiment, the second cleaning is performed with deionized water, and the cleaning time is selected from 10 minutes to 15 minutes, which is beneficial to removing chemical residues on the surface of the quartz component and improving the surface purity of the repaired quartz component.

[0053] It should be noted that the time for the first cleaning and the second cleaning can be the same or different; the temperature for the first cleaning and the second cleaning can be the same or different. Those skilled in the art can make a choice according to actual needs. To reduce costs, the present invention preferably performs cleaning at room temperature.

[0054] In one embodiment, the second drying is performed using a protective gas.

[0055] Preferably, the protective gas is selected from nitrogen.

[0056] The following specific examples will further illustrate the method for repairing the surface thermal properties of the quartz component. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, the conventional conditions or the conditions recommended by the manufacturer are followed. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0057] Example 1

[0058] First, the surface of the quartz component was sandblasted, and the quartz component was rinsed with deionized water for 10 minutes, and then dried with nitrogen to obtain the quartz component after sandblasting; the roughness of the surface of the quartz component was tested by atomic force microscopy. The initial roughness of the surface of the quartz component was 0.20μm, and the surface roughness of the quartz component after sandblasting was 1.54μm.

[0059] An acid solution for acid etching treatment was prepared, wherein the concentration of HF was 5%, the concentration of HNO3 was 10%, the concentration of H2SO4 was 10%, and the balance was water. The temperature of the acid solution was maintained at 30°C by heating, and the quartz component after sandblasting was completely immersed in the acid solution. After 60 minutes, the quartz component was taken out and rinsed with deionized water for 15 minutes, and then dried with nitrogen to obtain the quartz component after acid etching, whose surface roughness was 1.61 μm.

[0060] Example 2

[0061] The initial roughness of the surface of the quartz component is 0.20 μm. The surface of the quartz component is firstly sandblasted, and the quartz component is rinsed with deionized water for 15 minutes, and then blown dry with nitrogen to obtain a quartz component after sandblasting, and its surface roughness is 4.3 μm.

[0062] A solution for alkaline etching treatment was prepared, in which the concentration of sodium hydroxide was 2% and the balance was water. The solution temperature was maintained at 70° C. by heating, and the sandblasted quartz component was completely immersed in the alkaline solution. After 90 minutes, the quartz component was taken out and rinsed with deionized water for 15 minutes, and then dried with nitrogen to obtain a quartz component after alkaline etching, whose surface roughness was 3.9 μm.

[0063] Example 3

[0064] The initial roughness of the surface of the quartz component is 0.20 μm. The surface of the quartz component is firstly sandblasted, and the quartz component is rinsed with deionized water for 10 minutes, and then blown dry with nitrogen to obtain a quartz component after sandblasting, and its surface roughness is 5 μm.

[0065] A mixed solution for etching treatment is prepared, wherein the concentration of ammonium fluoride is 10%, the concentration of oxalic acid dihydrate is 8%, the concentration of H2SO4 is 5%, and the balance is water. Ammonium fluoride reacts slowly with oxalic acid to generate hydrofluoric acid. The etching reaction process is gentle and controllable. The solution temperature is maintained at 80°C by heating. The quartz component after sandblasting is completely immersed in the acid solution. After 600 minutes, the quartz component is taken out and rinsed with deionized water for 15 minutes. It is then blown dry with nitrogen to obtain a quartz component after acid etching, and its surface roughness is 4.6μm.

[0066] Comparative Example 1

[0067] The difference between Comparative Example 1 and Example 1 is that in the acid solution, the concentration of HF is 5%, and the balance is water. After the acid etching treatment, the light transmittance of the surface of the quartz component is obviously deteriorated and the surface is blurred.

[0068] The softening temperature of the quartz components obtained in Examples 1 to 3 was tested using a thermal expansion instrument. The temperature of the high-temperature furnace was increased at a rate of 10° C. / min. The test results are shown in Table 1.

[0069] Table 1

[0070]

[0071]

[0072] According to the results in Table 1, it can be seen that the initial softening temperature of the quartz parts is 1680°C. Under the same test conditions, the softening temperature of the quartz parts after sandblasting is significantly reduced to below 1395°C. After the etching treatment of Examples 1 to 3, the softening temperature of the quartz parts is significantly improved to above 1480°C, and its thermal performance is significantly improved. At the same time, according to the surface roughness of the quartz parts of Examples 1 to 3, it can be seen that the surface roughness of the quartz parts after sandblasting does not change much. In each embodiment, it is ensured that the difference between the surface roughness of the quartz parts after etching and the surface roughness of the quartz parts after sandblasting is ≤10%, and the adhesion ability of the surface of the quartz parts to the deposits is maintained.

[0073] In summary, the method for repairing the thermal properties of the surface of a quartz component provided by the present invention performs etching treatment through a specific solution, reacts with the quartz component through hydrofluoric acid or sodium hydroxide, and removes the water-insoluble fluorosilicate precipitate generated by the reaction of hydrofluoric acid and the quartz component through a first acid, effectively removes the sub-surface defects and the residual impurity layer generated during the sandblasting process, blocks the starting point of damage to the quartz component under high-temperature working conditions, improves the surface finish and purity, effectively restores the softening temperature of the quartz component, improves the thermal properties of the surface of the quartz component, and effectively guarantees the surface roughness of the quartz component, and improves the adhesion of the surface deposits of the quartz component. In addition, the repair method of the present invention has a simple process and has a wide range of application prospects.

[0074] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for repairing the thermal properties of a quartz component surface, characterized in that: The repair method comprises the following steps: The quartz parts are sandblasted, cleaned for the first time and blown dry for the first time; The quartz component after sandblasting is etched, and then cleaned and dried for the second time to obtain a repaired quartz component; wherein the etching solution used in the etching treatment is selected from a mixture of hydrofluoric acid, a first acid and water, or a mixture of sodium hydroxide and water, or a mixture of ammonium fluoride, oxalic acid dihydrate, a first acid and water.

2. The method for repairing the surface thermal properties of a quartz component according to claim 1, characterized in that: The surface roughness of the quartz component after sandblasting is 0.5 μm to 5 μm.

3. The method for repairing the surface thermal properties of a quartz component according to claim 1 or 2, characterized in that: The surface roughness of the quartz component after the sandblasting treatment is A μm, and the surface roughness of the quartz component after the etching treatment is B μm, wherein the absolute value of (AB) / A is less than or equal to 10%.

4. The method for repairing the surface thermal properties of a quartz component according to claim 3, characterized in that: The surface roughness of the quartz component after etching is 0.45 μm to 5.5 μm.

5. The method for repairing the surface thermal properties of a quartz component according to claim 1, characterized in that: The initial surface roughness of the quartz component is 0.1 μm to 0.2 μm.

6. The method for repairing the surface thermal properties of a quartz component according to claim 1, characterized in that: The etching solution includes 1% to 20% hydrofluoric acid, 1% to 50% first acid and the balance water; Alternatively, the etching solution includes 0.1% to 1% sodium hydroxide and the balance water; Alternatively, the etching solution includes 5% to 10% of ammonium fluoride, 5% to 10% of oxalic acid dihydrate, 1% to 50% of the first acid and the balance of water.

7. The method for repairing the surface thermal properties of a quartz component according to claim 1 or 6, characterized in that: The first acid is selected from at least one of nitric acid, hydrochloric acid, sulfuric acid and acetic acid.

8. The method for repairing the surface thermal properties of a quartz component according to claim 1, characterized in that: During the etching process, the temperature of the etching solution is 30° C. to 80° C.

9. The method for repairing the surface thermal properties of a quartz component according to claim 1, characterized in that: The etching treatment time is 10 minutes to 600 minutes.

10. The method for repairing the surface thermal properties of a quartz component according to claim 1, characterized in that: The first cleaning and the second cleaning are both performed with deionized water, and the cleaning time is independently selected from 10 min to 15 min; And / or, the first drying and the second drying are both performed using protective gas.

Citation Information

Patent Citations

  • Quartz surface chemical roughening treatment method

    CN110510886A

  • Method for producing matte glass, matte glass, and alkaline etching solution

    CN111116047A

  • Processing method of double-sided conduction microcircuit of glass substrate

    CN115190695A

  • Surface texturing treatment method for semiconductor quartz component

    CN116766065A

  • method for gettering a semiconductor wafer

    DE3922563A1